EXOGENOUS MELATONIN REVIVES THE LETROZOLE INDUCED TOXIC VARIATIONS IN BIOCHEMICAL PARAMETERS IN POLYCYSTIC OVARY SYNDROME IN RATS - BASHEER, MUDDASIR; RAI, SEEMA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Polycystic ovary syndrome (PCOS) is one of the most common reproductive and endocrine disorders in women of reproductive age. This study was commenced to elucidate the efficacy of melatonin in the pathogenesis of letrozole induced (PCOS) in Wistar rats. For this study albino rats were treated with Letrozole orally (1mg/kg) to induce PCOS condition. Total 24 rats were randomly selected for the experimental purpose and were divided into four groups viz. group I served as normal control, group II served as letrozole treated, group III served as melatonin treated and group IV served as letrozole and Melatonin treated. On the completion of experimental period of 35 days, animals were sacrificed. Ovaries of all respective groups were dissected out and processed for the assessment of biochemical variables viz. lipid peroxidation (LPO), antioxidative system; superoxide dismutase (SOD), reduced glutathione (GSH) and Catalase (CAT) activity, total protein quantification and lipid parameters (Total Cholesterol, Triglycerides, high density lipids, low density lipids and very low density lipids). Letrozole administration in group II led to significant increase in lipid peroxidation, total protein content and lipid profile and a significant decrease in antioxidant activity. However, administration of melatonin in group IV resulted in the recovery of these parameters significantly towards the normal comparable to the control group. Therefore, melatonin might be suggested as a protective molecule against letrozole induced PCOS condition.